Highly efficient synthesis and separation of fuel precursors from the concentrated ABE fermentation broth in a biphasic catalytic process. (15th April 2019) - Xie, Shaoqu; Fu, Chuhan; Song, Wenli; Zhang, Yulei; Yi, Conghua
Graphical abstract: Highlights: One-pot synthesis and separation of C5 –C11 fuel precursors from ABE. ABE are converted into large ketone molecules in the distillation process. The salting-out effect of K3 PO4 induces the liquid-liquid phase splitting. More than 99.5% of water from the concentrated fermentation broth was removed. Tuning the reaction conditions can obtain C5 –C7 or C9 –C11 products as the main. Abstract: Developing a simple and efficient process for the conversion of biomass to petrol, diesel and jet fuels are our urgent mission due to the limitation of fossil fuels. Biobutanol is an important biomass-derived biofuel that can be converted to longer-chain petrol-range, diesel-range and jet-range fuels. Basing on the obtained concentrated acetone-1-butanol-ethanol (ABE) fermentation broth through a prefractionator, we report a palladium-catalysed alkylation of acetone with ethanol and 1-butanol to more efficiently produce C5 –C11 fuel precursors in a reactor, where all the precursors and reactants were separated simultaneously by the salting-out effect of K3 PO4 . The precursors include ketones and a small amount of alcohols that can be reduced to alkanes for use as liquid transportation fuels. Tuning the reaction conditions can obtain different proportions of C5 –C7 products (monoalkylation) and C9 –C11 products (double alkylation) and the overall product contents accounted for up to 82 wt%. More than 99.5% of water from the concentrated ABE fermentation broth was removed by the salting-out effect of K3 PO4.